Influencia de las dosis de ceniza de madera, en las características agronómicas y rendimiento de Capsicum baccatum l. “Ají Amarillo”, Zungarococha Loreto. 2019 - Mendoza Severiano, Juan Moises (2022)
ood ash is an optimal fertilizer for the planting of olericolas crops, rich in potassium and phosphorus so it was used in the cultivation of Capsicum baccatum L. "yellow pepper" and in this sense its study was developed on its influence with different doses of wood ash in the present crop, evaluating its agronomic characteristics and yield, making use of Completely Random Block Statistical Design, the Analysis of Variance, Tukey’s Comparisons test in the Zungarococha area south of the city of Iquitos in a sandy loam textured soil whose results led to the following conclusions: Fertilization with doses of wood ash influenced the agronomic characteristics and yield of Capsicum baccatum L. "yellow pepper"; Treatment T4 (3 t of wood ash/ha), presented the highest average values of length, diameter, number of fruits, fruit weight and fruit weight/ha ikewise, it presented the best average weight of fruits / ha with 36,290 t / ha and the best profitability with S / .171,291.5.